Parental Methods in Habituating Children to Pray Before Engaging in Activities - Zr, Jamilah; Pratiwi, Sindi; Selian, Suci Nadillah; Sit, Masganti (The Future of Education Journal, 2024)
This study discusses methods of teaching and habituating prayer for young children through continuous and consistent habituation. Habituation is crucial for young children because their memory is still weak and their attention is easily diverted. The habituation method, known as operant conditioning, aims to accelerate the internalization of values being taught, so that these values are permanently embedded in the child’s character. This habituation also forms the foundation of character education, which emphasizes teaching positive values, one of which is the habit of praying. The process of habituating prayer for young children involves steps such as providing direct examples, using prayer songs, telling inspirational stories, and establishing enjoyable prayer routines. Praise and rewards are also given to reinforce the habit. The benefits of teaching prayer to young children include building faith, instilling moral and ethical values, developing emotional calmness, and promoting discipline and positive habits. Parents, as the first educators, play a crucial role in habituating their children to pray by providing good examples, offering clear explanations about prayer, and applying proper prayer etiquette. With these methods, it is hoped that children can make prayer a good habit and develop spiritual intelligence and positive character.